ENT 530 Azy's Kuah Laksa Pekat / Nur Balqis Abdul Rahim ... [et al.] - Abdul Rahim, Nur Balqis; Shaharuddin, Nur Fatin Adila; Mohamed, Nur Natasya Izlin; Mohd Nizam, Nur Rabiatul Adawiyah; Mohd Saad, Nurul Izzah; Khairudin, Rasyiqa Adlinna (2019)
In this case study, the business of Azy's Laksa Kuah Pekat was studied to analyse problems relate the theory to a practical situation. There are few problems in Azy's Laksa Kuah Pekat business such as problem in obtaining supplier and problem in human resources. As to solve the situation, a few problem solving statements are suggested to these major problems. For example, if get problem with supplier then we suggest to change from fix supplier to a flexible supplier, as for the problem in human resources then we suggest to find workers and do a delivery service. As for the solution to the problem, the best recommendation is to be implemented. The strength, weakness, opportunity and threat of the business was analysed by using SWOT analysis.